P-GaN/n-ZnO nanorods: the use of graphene nanosheets composites to increase charge separation in self-powered visible-blind UV photodetectors. (30th August 2018) - Huang, Chun-Ying; Kang, Chun-Chieh; Ma, Yu-Chi; Chou, Yu-Cheng; Ye, Jian-Huei; Huang, Ru-Ting; Siao, Chen-Zih; Lin, Yu-Ching; Chang, Yu-Hao; Shen, Ji-Lin; Lin, Tai-Yuan
Abstract: ZnO-based heterojunctions have found applications as self-powered ultraviolet photodetectors (PDs). However, high doping levels are not compatible with high mobility for metallic doped ZnO-based PDs so further development has been inhibited. This study demonstrates a method to increase the open-circuit voltage ( V oc ) that allows keeping a sufficiently high level of mobility of ZnO, using a ZnO nanorod/GaN heterojunction that incorporates graphene nanosheets as the active layer. These hybrid PDs have triple the value for V oc of PDs that have only pure ZnO and better exhibit photo-response characteristics. The results of surface Kelvin probe microscopy and x-ray photoelectron spectrometer show that the complex defects that occur because Zn interstitials form a shallow donor in ZnO are mainly responsible for the increase in the value of V oc . Using this functional nanostructure as an active layer represents a new method for the manufacture of high-performance self-powered PDs.